REKONSTRUKSI RUANG LINGKUP KEWENANGAN PRAPERADILAN DALAM SISTEM PERADILAN PIDANA INDONESIA (Jurnal Magister Hukum Perspektif, 2019)
Pre-trial is part of the criminal justice system regulated in KUHAP which normatively regulates the authority of the local district court to investigate and decide whether the arrest and / or deprivation of liberty is legal or not, or the request of the suspect or his family or other parties or representatives of the suspect; whether termination of investigation or prosecution is lawful upon request; as well as requests for compensation or rehabilitation submitted by the suspect or his family or other parties or attorneys whose cases are referred to the local district court for compliance with law and trial, but in fact there are pretrial regulations other than KUHAP which result in the expansion of pretrial authority, this article uses juridical normatives method, with statute approach and conceptual approach, for analyst some regulation of law about pretrial hearing for find new construct about limitation pretrial hearing in criminal justice system. Keywords : pretrial hearing, suspect, investigation, authority